1980
DOI: 10.1007/bf01402078
|View full text |Cite
|
Sign up to set email alerts
|

Predicting lethal outcome after severe head injury ? A computer-assisted analysis of neurological symptoms and laboratory values

Abstract: A total number of 58 parameters (laboratory values, neurological symptoms, and vegetative parameters) were evaluated in 150 patients during the first seven days after severe head injury. The patients were divided into two groups, "survivors" and "non-survivors". Eight easily evaluable routine parameters with the most significant differences between the two groups of patients were used for statistical evaluation of a "no survival chance score". These highly indicative parameters are serum osmolarity and urea, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1983
1983
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Fever is associated with a worse outcome after brain injury. [26][27][28] A recent meta-analysis showed that in patients with ischemic stroke, fever is associated with a marked increase in morbidity and mortality. [29][30][31][32][33][34] Few studies have examined the relationship of fever and outcome in patients with intracerebral Deogaonkar et al: Fever after intracerebral hemorrhage hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…Fever is associated with a worse outcome after brain injury. [26][27][28] A recent meta-analysis showed that in patients with ischemic stroke, fever is associated with a marked increase in morbidity and mortality. [29][30][31][32][33][34] Few studies have examined the relationship of fever and outcome in patients with intracerebral Deogaonkar et al: Fever after intracerebral hemorrhage hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…We try to check all our own developments for negative side-effects and there are successful programs that were never put into clinical operation because we could not exclude the possibility of harmful results (e.g. predicting lethal outcome after severe head injury [25]). To counter negative side-effects we also engage in policy setting, normative work and education for data protection, telemedicine etc.…”
Section: Professional Responsibility In Medical Informaticsmentioning
confidence: 99%